Implementasi media pembelajaran tematik audio visual untuk meningkatkan hasil belajar siswa kelas V di SD Negeri Majingklak 04 tahun pelajaran 2020/2021 - Siti Nurhomsah (Jurnal Kualita Pendidikan, 2020)
This research was conducted with a classroom action research design to improve and improve student learning outcomes through the implementation of thematic learning media using audio visuals. This research was conducted in class V SD Negeri Majingklak 04 in the academic year 2020/2021, with 15 students. This study aims to determine whether learning using audio-visual media (youtube video) can improve student learning outcomes and learning activities. The focus in this study is the learning outcomes of theme 4 Healthy is Important which includes cognitive, affective, psychomotor aspects, as well as learning activities and student skills, as well as teacher performance. The results showed an increase in student learning outcomes, with an average score of 73.3 in cycle 1 to 80 in cycle II. Student activity also increased as seen by the interaction and courage of students in presenting their work in front of the class. It can be concluded that learning theme 4 Healthy is Important through the implementation of learning media using audiovisual media can improve learning outcomes and student learning activities.